100 cases in clinical medicine - Rees, John, 1949-; Pattison, James M.; Kosky, Christopher (100 cases., 2014)
Preface Most doctors think that the most memorable way to learn medicine is to see patients. It is easier to recall information based on a real person than a page in a textbook. Another important element in the retention of information is the depth of learning. Learning that seeks to understand problems is more likely to be accessible later than superficial factual accumulation. This is the basis of problem-based learning, where students explore problems with the help of a facilitator. The cases in this book are designed to provide another useful approach, parallel to seeing patients and giving an opportunity for self-directed exploration of clinical problems. They are based on the findings of history taking and examination, together with the need to evaluate initial investigations such as blood investigations, X-rays and ECGs. These cases are no substitute for clinical experience with real patients, but they provide a safe environment for students to explore clinical problems and their own approach to diagnosis and management.